2021
DOI: 10.5565/rev/educar.1126
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Mission Statements to School Practice and Professional Development: An Interpretative Phenomenological Analysis

Abstract: While mission statements (MSs) are included in schools often due to governing policy, evidence suggests they remain underutilized by leaders. Scant research is undertaken with regard to school mission statements and how these affects daily practice. This qualitative phenomenological study explores the extent to which school MSs influence daily practice, as well as professional development for school leaders and teachers. This study draws upon interviews with six individuals who lead or teach at two different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…Knowing a mission statement can make it motivational (Bartkus et al, 2000). Like the current study, other authors found graduate students in educational administration programs did not know the mission statement, and both studies stated there was still a benefit from mission statements (Gurley et al 2015;Watkins & McCaw, 2007).Another small study (N = 6) in the Philippines found similar results: Though many participants did not know the mission statement of one's school, there was a known-unknown (Ransom &Vlachopoulos, 2021). The current study deviated because it did not make the unsubstantiated claim unknown mission statements were important and should be taught more.…”
Section: Results Of Experiential Phenomenological Studysupporting
confidence: 72%
“…Knowing a mission statement can make it motivational (Bartkus et al, 2000). Like the current study, other authors found graduate students in educational administration programs did not know the mission statement, and both studies stated there was still a benefit from mission statements (Gurley et al 2015;Watkins & McCaw, 2007).Another small study (N = 6) in the Philippines found similar results: Though many participants did not know the mission statement of one's school, there was a known-unknown (Ransom &Vlachopoulos, 2021). The current study deviated because it did not make the unsubstantiated claim unknown mission statements were important and should be taught more.…”
Section: Results Of Experiential Phenomenological Studysupporting
confidence: 72%
“…Like the current study, other authors found graduate students in educational administration programs did not know the mission statement, and both studies stated there was still a benefit from mission statements (Gurley et al 2015;Watkins & McCaw, 2007). Another small study (N = 6) in the Philippines found similar results: Though many participants did not know the mission statement of one's school, there was a known-unknown (Ransom & Vlachopoulos, 2021). The current study deviated because it did not make the unsubstantiated claim unknown mission statements were important and should be taught more.…”
Section: Results Of Experiential Phenomenological Studysupporting
confidence: 52%